Effect of the excitation setup in the improved enhancement factor of covered-gold-nanorod-dimer antennas - Ramos, Iván A. (2022)
Devices possessing the ability to sense both electrically and optically molecular targets are of fundamental and technological interest. Towards this end, it has been shown that covering the ends of gapped gold-nanorod-dimer nanoantennas can improve the enhancement factor (EF) that quantifies the nanoantenna efficiency for surface-enhancement Raman spectroscopy (SERS) for an incident wave coming from the top of the sample. Here, as the covering breaks the top-bottom symmetry, we investigate the behaviour of the EF for excitation coming from the bottom of the sample. This is relevant in presence of a reflecting substrate or due to the placement of the device in a cavity field. We also study the case of a superposition of waves coming from both directions in the limit cases in which a node or an antinode of the total incident field lies at the center of the gold nanorods. In all these situations we find that the EF of the covered device can continue to be higher than for the uncovered case when the geometrical parameters are tuned to the peak values of the calculated enhancement factor.